The Impact of Workload, Burnout, and Organizational Commitment on Cyberloafing Actions - Maya Sri Anindita; Arthur Sitaniapessy; Joko Rizkie Widokarti (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
This study analyzes the influence of workload, burnout, and organizational commitment on cyberloafing actions. The rapid advancement of technology has led to significant changes in work patterns. A negative effect of internet technology is the indication that internet usage has no relation to work-related interests (cyberloafing). Increasing workloads have caused burnout and impacted organizational commitment. The method used in this research is quantitative. The test results show that, of the three hypotheses tested, one hypothesis was not supported, namely the effect of workload on cyberloafing." This study concludes that organizations need clear regulations and internet usage monitoring. Development and training are also necessary to build a culture of innovation and creativity.